1982
DOI: 10.1007/bf00213765
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid-contacting neurons and other somatostatin-immunoreactive perikarya in brains of tadpoles of Xenopus laevis

Abstract: In untreated tadpoles of Xenopus laevis, stage 60 (Nieuwkoop and Faber 1956), somatostatin-immunoreactive perikarya and fiber networks are already discernible in the pallium and the septum, as well as in the anterior and posterior hypothalamus. In addition, somatostatin-immunoreactive cerebrospinal fluid (CSF)-contacting neurons were found in the periventricular gray of the most caudal division of the ventral tuber cinereum. The results are discussed with respect to the inhibitory influence of the system of CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…A second type of CSF-contacting dendritic terminal was also demonstrated ultrastructurally (VIGH-TEICHMANN et al, 1976a). Presumably, some of these cells correspond to somatostatinimmunoreactive nerve cells observed in Carassius auratus (KAH et al, 1982), Anguilla anguilla, Salmo gairdneri, Phoxinus phoxinus (VIGH-TEICHMANN, et al, 1983c), Rana temporaria, R. catesbeiana, Triturus cristatus and Xenopus laevis (VANDESANDE and DIERICKX 1980;FASOLO and GAUDINO, 1981;BLAHSER et al, 1982;YUI,1983). Previously, LHRH-positive CSF-contacting neurons were also observed in the preoptic nucleus of cyclostomes and Gasterosteus aculeatus (GRIM et al, 1979a, b;BORG et al, 1982).…”
Section: Neuronsmentioning
confidence: 92%
See 1 more Smart Citation
“…A second type of CSF-contacting dendritic terminal was also demonstrated ultrastructurally (VIGH-TEICHMANN et al, 1976a). Presumably, some of these cells correspond to somatostatinimmunoreactive nerve cells observed in Carassius auratus (KAH et al, 1982), Anguilla anguilla, Salmo gairdneri, Phoxinus phoxinus (VIGH-TEICHMANN, et al, 1983c), Rana temporaria, R. catesbeiana, Triturus cristatus and Xenopus laevis (VANDESANDE and DIERICKX 1980;FASOLO and GAUDINO, 1981;BLAHSER et al, 1982;YUI,1983). Previously, LHRH-positive CSF-contacting neurons were also observed in the preoptic nucleus of cyclostomes and Gasterosteus aculeatus (GRIM et al, 1979a, b;BORG et al, 1982).…”
Section: Neuronsmentioning
confidence: 92%
“…In birds, only one type of CSF-contacting nerve cells could be demonstrated (granular vesicles, 130-140 nm in diameter; VIGH-TEICHMANN et al, 1971b). Further studies are required to clarify whether the CSF-contacting neurons correspond to gastrin-, somatostatin-or VIPimmunoreactive elements previously observed in Xenopus laevis and Coturnix coturnix (DOERR-SCHOTT et al, 1979;BLAHSER et al, 1982;YAMADA et al, 1982).…”
Section: Neuronsmentioning
confidence: 95%
“…CSF-CNs receive, transform, and transmit non-synaptic signals from the CSF to neurons and glia in the parenchyma of the brain [104,[111][112][113][114][115]. CSF-CNs are universally present in vertebrates, and constitute a phylogenetically ancient structure that enables communication between distant elements of the nervous system via non-synaptic signals carried in the CSF [104,105,[108][109][110][111][112][113][115][116][117][118]. A marvelous evolutionary hypothesis traces back CSF-CNs from mammals to reptiles; and then to the fluid-contacting neurons of marine organisms, from the CSF-CNs of cyclostomes, and further back to neurons in larval lancelets that contact a central canal enveloping seawater [104].…”
Section: Rapid Signal Transduction Into Neuronal Network Via Cerebromentioning
confidence: 99%
“…It has been subsequently found that somatostatin is widely distributed in the central nervous system (CNS), the pancreas, and the gastrointestinal tract, where it acts as a neurotransmitter/ neuromodulator and a hormone (for review, see Epelbaum et al, 1994;Viollet et al, 2000). The distribution of somatostatin in the CNS has been described in various vertebrate taxa, including mammals (for review, see Johannson et al, 1984), birds (Hoffman and Hayes, 1979;Takatsuki et al, 1981;Blä hser, 1984;Trabucchi et al, 2003), reptiles (Doerr-Schott and Dubois, 1977;Fasolo and Gaudino, 1982;Bear and Ebner, 1983;Weindl et al, 1984;Reiner and Oliver, 1987), amphibians (Rémy and Dubois, 1978;Vandesande and Dierickx, 1980;Inagaki et al, 1981;Blä hser et al, 1982;Yui, 1983;Olivereau et al, 1984c;Adli et al, 1988;Laquerrière et al, 1989;Vallarino et al, 1998;Petko and Orosz, 1996;Stuesse et al, 2001), and several groups of fishes, i.e., lungfish (Vallarino et al, 1997;Trabucchi et al, 1999), teleosts (Olivereau et al, 1984a,b;Verdonck and Ollevier, 1984;Lin et al, 1999), chondrosteans (Trabucchi et al, 2002), elasmobranch (Nozaki, 1985), and in cyclostomes (Nozaki and Gorbman, 1983;Wright, 1986;Cheung et al, 1991;Yañ ez et al, 1992). Somatostatin-like immunoreactivity h...…”
mentioning
confidence: 97%